1995
DOI: 10.1111/j.1530-0277.1995.tb01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate‐Deficient Transferrin in Alcohol and Nonalcohol Abusers with Liver Disease

Abstract: Carbohydrate-deficient transferrin (CDT) has been demonstrated to be a marker of prolonged heavy alcohol consumption. We compared this marker with gamma-glutamyltranspeptidase (GGT) and mean corpuscular volume (MCV) in alcohol and nonalcohol abusers with liver disease. Our results confirm that the sensitivity of CDT in alcoholics is high, although lower than that of GGT and MCV; however, the specificity of CDT was higher than that of the other two markers. This finding supports the notion that CDT is only part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…For example, one study found CDT levels elevated in early alcoholic liver disease but low levels of CDT in the advanced stages of alcoholic liver disease (Niemela, 1995). In contrast, another study found nearly 30% of patients with severe liver disease, but not drinking alcohol, had positively elevated CDT values compared to only 3% of non-drinking controls without liver disease (Meregalli, 1995). Clinical assessments and definitions of serious liver disease may be subjective.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, one study found CDT levels elevated in early alcoholic liver disease but low levels of CDT in the advanced stages of alcoholic liver disease (Niemela, 1995). In contrast, another study found nearly 30% of patients with severe liver disease, but not drinking alcohol, had positively elevated CDT values compared to only 3% of non-drinking controls without liver disease (Meregalli, 1995). Clinical assessments and definitions of serious liver disease may be subjective.…”
Section: Discussionmentioning
confidence: 97%
“…The %CDT, used in this study, reports the CDT as a percentage of the total transferrin which would be preferable and more accurate in these cases as it takes into account the transferrin status. Some of the prior studies of CDT and liver disease did not use the %CDT and had equivocal results (Niemela, 1995, Meregalli, 1995.…”
Section: Discussionmentioning
confidence: 99%
“…False positive results for CDT can be caused by an inborn error of glycoprotein metabolism, pregnancy, genetic D-variant of transferrin, and severe liver diseases (1,4,9). On the other hand, increased GGT values have been reported in response to most hepatobiliary disorders, obesity, diabetes, and hypertriglyceridemia (8,(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Although CDT is usually unaffected by the presence of liver disease, false-positive results have been reported in primary biliary cirrhosis and in patients with severe non-alcohol-related hepatic failure (72,73,74). Complementary methodologies have been employed to reduce the number of CDT falsepositives.…”
Section: Preanalytical Variationsmentioning
confidence: 99%